2010
DOI: 10.1016/j.jcrs.2010.07.017
|View full text |Cite
|
Sign up to set email alerts
|

New factor to improve reliability of the clinical history method for intraocular lens power calculation after refractive surgery

Abstract: The regression formula determined whether the refraction depended on the onset of cataract and estimated the amount of undercorrection or overcorrection that occurred after refractive surgery, leading to improved estimation of the power of the IOL to be implanted. It may allow the use of history-related formulas in IOL power calculation for eyes that have had corneal refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…13 A correlation between refractive error, AL and K readings has been described. 14,15 In the present study, we found a slightly significant difference in the AL*K between the two eyes, mainly in the higher myopic patients (higher AL*K) (Figure 3). This could depend on the fact that this product cannot precisely reflect the refractive error, because it depends also on the power of the crystalline lens and its position.…”
Section: Discussionsupporting
confidence: 49%
“…13 A correlation between refractive error, AL and K readings has been described. 14,15 In the present study, we found a slightly significant difference in the AL*K between the two eyes, mainly in the higher myopic patients (higher AL*K) (Figure 3). This could depend on the fact that this product cannot precisely reflect the refractive error, because it depends also on the power of the crystalline lens and its position.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, an accurate subjective measurement of refractive error is indispensable. 13,14 The refractive state of the patient is not always stable, and this was the reason why manifest refraction was measured repeatedly in this study. However, cycloplegic refraction may have increased the accuracy further.…”
Section: Discussionmentioning
confidence: 98%
“…The same authors, recently, proposed a modification to this method [70]: the power of the IOL should be calculated using the SRKT formula for all axial lengths utilizing the correction factor described above, but in case the product of AL (axial length) ∗   K mis (corneal power measured with a common keratometer) is >1060, the IOL power obtained shall be reduced using the following regression formula: Y=(normal0.0157ALKmis+normal16.437), where Y is refractive error to insert in the IOL power calculation to obtain emmetropia.…”
Section: Resultsmentioning
confidence: 99%